Promoting the 21st Century Skills Using Project-Based Learning (Universitas Negeri Semarang, 2023)
The requirement of the 21st century demands teachers to design a learning process that emphasizes student-centered learning. Project-based learning is seen as an effective model to solve this problem. Therefore, this study aimed at analyzing the use of project-based learning viewed from its characteristics, syntax, advantages, and disadvantages. This study was designed in a library study in which the data were obtained from reviewing some articles related to the topic. The results of the study showed that 1) the main characteristic of this model is the project itself which is guided by a real problem or question; 2) in general, the syntax of project-based learning can be categorized into three, that is, planning, implementing, and evaluating; 3) the advantages of this model meet the 21st century skills; 4) the disadvantages of this model mainly deal with time allotment, students’ characteristics, and school facilitation. In conclusion, project-based learning is an effective model to promote 21st century skills.